Tourenplanung mit alternativen Lieferperioden und Teillieferungen - Breier, Heiko (Wissenschaftliche Berichte des Instituts für Fördertechnik und Logistiksysteme des Karlsruher Instituts für Technologie, 2014)
This book examines the Vehicle-Routing-Problem with split-deliveries and alternative delivery periods (SDVRPA). It is solved with a Branch-and-Price-Algorithm. When alternative delivery periods and split-deliveries are employed, freight forwarders get a wider scope for planning and can therefore plan more efficient routes. Even with few alternative delivery periods, which allow vehicles to be used more efficiently, substantial savings can be achieved.